Multiple cutaneous necrotic lesions associated with Interferon beta-1b injection for multiple sclerosis treatment: A case report and literature review - Gita Faghihi; Akram Basiri; Mohsen Pourazizi; Bahareh Abtahi-Naeini; Ali Saffaei (Wolters Kluwer Medknow Publications, 2015)
Multiple sclerosis (MS) is a chronic and debilitating inflammatory autoimmune disorder of the central nervous system. MS patients may experience severe local inflammatory skin reactions during disease-modifying therapy with subcutaneously injected interferon-beta-1b (IFN-β). We report the case of a 49-year-old woman with relapsing-remitting MS, who developed multiple cutaneous necrotic ulcers on both arms and thighs after 3 months of treatment with subcutaneous IFN-β-1b. The biopsy specimens showed skin and subcutaneous tissue necrosis. We diagnosed the skin lesions as cutaneous necrotic ulcerations associated with IFN-β-1b injection. The treatment included ending the use of subcutaneously injected IFN-β-1b and switching to intramuscularly injected IFN-β-1a because of the multiple cutaneous necrotic ulcers. The injection of IFN-β-1b in the areas with lesions was stopped, and the patient's clinical condition improved with the addition of routine wound care, surgical debridement, and skin grafting. This report is intended to raise awareness about severe adverse skin reactions which may rarely occur with subcutaneous IFN-β-1b injection. Early recognition and correction of the injection technique and switching to other forms of interferon can help to prevent these complications.